Characterization of “sweet spots” and optimization of volume fracturing parameters in deep tight reservoirs of Subei Basin - TANG Jiandong, ZHANG Shunkang, LIN Shiwei, GE Zhengjun, LIN Bo (Youqicang pingjia yu kaifa)
In line with the strategy of “finding oil layers beneath oil layers”, exploration and development in the Jiangsu Oilfield have progressively extended into deeper formations. Deep, tight, and ultra-low permeability reservoirs in northern Jiangsu have become key targets for reserve enhancement and production expansion. However, due to complex structural settings, sedimentary conditions, and natural fractures, the effective utilization of these reservoirs remains highly challenging. This study conducted research on the effective utilization of deep tight reserves in northern Jiangsu. For “sweet spot” characterization, an integrated geological-seismic approach was developed by synthesizing multidisciplinary data from geology, geophysics, reservoir engineering, engineering, and economics. A multi-parameter comprehensive characterization and evaluation methodology was established for tight sandstone reservoirs, accurate delineation of tight reservoirs and effectively guiding reservoir classification and “sweet spot” selection. For volume fracturing, engineering techniques were implemented such as increasing fracture-controlled volume, using temporary plugging and diversion to enhance fracture complexity, and employing combined proppant injection to increase fracture filling volume. These techniques were further optimized based on the characteristics of specific reservoir blocks, resulting in a preliminary volume fracturing technology tailored to the deep tight reservoirs of Jiangsu. To optimize development strategies, well types, production methods, fracturing parameters, and well pattern designs were systematically refined to ensure stable production. For more efficient and cost-effective drilling, improvements in drilling techniques and well placement schemes were introduced, achieving accelerated drilling speed and cost reductions. The study provided effective guidance for field implementation. A total of 7 conventional wells and 1 horizontal well were drilled in block X17, block F125, and block Y48. The average daily oil production per conventional well exceeded 6 tonnes, while the horizontal well maintained a stable daily output of over 10 tonnes. The results demonstrate the effective utilization of deep tight reserves in northern Jiangsu. The research methodology and field practices can provide technical references for the development of other tight oil resources.